Match-play running performance and exercise intensity in elite international women's rugby sevens - Malone, S.; Earls, M.; Shovlin, A.; Eddy, A.; Winkelman, N. (The Journal of Strength and Conditioning Research, 2020)
The aim of the current investigation was to describe the running and physiological performance demands of elite women's rugby sevens match-play. Twenty-seven (n = 27) rugby seven's players (24.4 ± 2.1 years; 168 ± 7.1 cm; 67.9 ± 4.3 kg) were recruited for the current investigation. Across the observational period, 36 games were analyzed; during these games, players wore global positioning system technology (10-Hz, Statsports Viper Pod; STATSports, Newry, Northern Ireland, United Kingdom) and heart rate monitors (Polar Team System, Polar Electro Oy, Kempele, Finland). A total of 250 individual player data sets were obtained for final analysis. Players were categorized based on positional groups; backs and forwards, and monitored across halves of play. The mean distance covered during match-play was 1,625 ± 132 m which equates to a relative running performance of 116.1 ± 9.4 m/min. The high-speed distance of players was 199 ± 44 m, which equates to a relative high-speed running performance of 14.2 ± 3.1 m/min. Significant reductions in high-speed running (p = 0.003; effect size [ES]: 0.23; 90% confidence interval [CI]: 0.11-0.41) and significant increases in lower speed running were observed across halves of play (p = 0.04; ES: 0.33; 90% CI: 0.16-0.54). Across the duration of match-play, players spent over 75% of the time above 80% of heart rate maximum (HRmax). Backs were found to have a higher reduction in total distance (p = 0.345; ES: 0.21; 90% CI: 0.11-0.31), high-speed distance (p = 0.04; ES: 0.61; 90% CI: 0.48-0.77), sprint distance (p = 0.034; ES: 0.11; 90% CI: 0.02-0.21), and average sprint distance (p = 0.03; ES: 0.33; 90% CI: 0.08-0.44) across halves of play when compared to forwards. Normative data are now provided to coaches who need to consider the positional differences in running and physiological performance when constructing training drills for seven's players.